Customer Satisfaction in Using Shopee Marketplace: Gender based Comparison - Prataga, Dimas Ikbal; Santoso, Ignatius Hari (International Business Management - Universitas Ciputra, 2022)
This study analyzes the information quality, perceived price, and system quality predictors of Shopee customer satisfaction. Also, in this research, we test gender as a moderator construct. This study used 100 samples. Using Smart PLS version 3, we can find that three latent constructs are significant predictors of Shopee customer satisfaction. However, gender as a moderator cannot have a significant effect. For further research, we suggest the additional construct, such as online review to be tested as a predictor. Keywords: information quality, perceived price, system quality